Multiscale Evaluation System for Cold Patch Asphalt Mixtures: Integrating Macro-Performance Tests and Meso-Structural CT Analysis - Wenbin Xie; Li Li; Runzhi Yang (Applied Sciences)
The absence of standardized evaluation criteria for cold patch asphalt mixtures (CPAMs) leads to arbitrary material selection in pavement pothole repair, resulting in premature failure and recurrent damage. This study develops a comprehensive evaluation framework combining macro-performance tests with X-ray computed tomography (CT)-based meso-structural analysis. The macroscopic evaluation system incorporates six key parameters: aggregate gradation, binder–aggregate ratio, penetration strength, molding strength, residual rate, and stability retention. The CT-based meso-structural assessment quantifies void characteristics (longitudinal distribution, radial distribution, fractal dimension) and aggregate skeleton features (contact points, coordination number) through 3D reconstruction. Experimental results demonstrate that optimizing asphalt content (4.5–4.7%) with adjusted critical aggregate fractions (4.75 mm:35.0–45.0%; 2.36 mm:30.0–40.0%; 13.2 mm:1.0–1.2%; 9.5 mm:10.0–15.0%) significantly enhances repair durability. The established multiscale evaluation methodology provides a theoretical foundation for developing standardized CPAM quality specifications, particularly in emergency maintenance scenarios.